SETTLING IN NEW LAND IN HA-JIN'S SHORT STORIES COLLECTION A GOOD FALL (2009) - Asih Anggraini; Kurnia Ningsih (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of settling in new land which is done by Chinese immigrants in United States and to know he contribution of character, plot (conflict), and setting in revealing the settling in new land. This analysis is related to the adaptation concept by Wiiliam Butler Yeats in postcolonial approach that is supported by the text and conotext based interpretation. The result of this analysis shows two different characters succeeds to settle in new land that can be seen through their ways of self-adaptation and hard work.